MICROWAVE-MEDIATED EXTRACTION OF LANTANA CAMARA (L) WITH COW URINE - SHIRPURKAR, YASHIKA; S, VENKATESAN JAYAKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: There are approximately 150 species of perennial blooming plants in the Verbenaceae family, which includes Lantana camara (L). The instantaneous preparation of the cow urine extract in the microwave, followed by the partition process of making different solvent crude extracts, and subsequent investigation of the biological efficacy against bacterial strains Pseudomonas aeruginosa, Salmonella typhimurium, Staphylococcus aureus, and Escherichia coli by disk diffusion method, constitutes the main goals. Additionally, thin-layer chromatography (TLC), IR, and phytochemical studies will be used to analyze the contents of the phytochemicals. Methods: The development of a plant profile comprises authentication, collecting, synthesis of a cow urine extract, and biological analysis. Phytochemical, TLC, and IR spectral methods were used to validate the presence of phytoconstituents in the solvent crude extracts. Results: It is shown that microwave method improves the yield when compared to cold percolation method and the maximum zone of inhibition shown by the crude extract is compared to standard and control. Among the three extracts, chloroform extract displayed promising inhibitory action against four bacterial strains. Further IR spectra absorption peaks provide evidence of the kind of functional groups present. Conclusion: The current novel research demonstrates that an efficient way for producing bioactive extract in short time and with a higher yield is due to the combination of microwave irradiation with cow urine. In vitro screening of crude extracts of the leaf of the plant shows promising activity against bacterial strains and thus suggests its application in drug discovery research.